“911” among West African immigrants in New York City: A qualitative study of parents’ disciplinary practices and their perceptions of child welfare authorities - Rasmussen, Andrew (2012)
Immigrant parents’ perceptions of child protective services may have important implications for their engagement in public institutions that are central to their children’s well being. The current study examined West African immigrants’ perceptions of child welfare authorities and the role of disciplining and monitoring in these communities’ meaning making. A multiethnic group of 59 West African immigrants (32 parents and 27 adolescent children) living in the United States were interviewed in 18 focus groups and eight individual interviews between December 2009 and July 2010. Data were analyzed using a grounded theory approach; strategies for rigor included triangulation (multiple interview formats, varied composition of groups, multiple coders for each transcript), verification (follow-up interviewing, feedback to community-based organizations), and auditability. Primary among parents’ concerns were “911” (used to refer to the police and child protective authorities), the loss of collective child monitoring networks, and threats to their children posed by “American” values and neighborhood violence. Children were concerned with parents’ close monitoring that resulted in boredom and a sense that parents did not recognize them for adhering to their families’ values. Feedback from CBOs suggested that parents got their information about child protective policies from children but that although misinformed they were accurate in their negative assessment of contact. Not unlike in other urban populations, West African immigrants’ disciplinary tactics are instrumental, oriented towards protecting their children from the multiple dangers perceived in their surroundings, but may also put them at risk for contact with child protective services. Results suggest that “911” results from a “loss spiral” (Hobfoll, 1989) that begins as West Africans resettle without collective child monitoring networks, leading to increased concern for their children’s safety, and interacting with a school-home disciplinary mismatch that may increase the likelihood of contact with child protection. Hobfoll, S. (1989). Conservation of resources theory: A new attempt and conceptualizing stress. American Psychologist, 44(3), 513–524.